Disorders of puberty. (September 2017) - Hendriks, Emile; Prentice, Philippa; Williams, Rachel
Abstract: Puberty is the process of development of adult secondary sexual characteristics. Disorders of puberty can be classified into early (precocious) and late (delayed) puberty. Early (precocious) puberty can be secondary to either activation of the hypothalamic-pituitary-gonadal axis (gonadotrophin-dependent, or central) or altered regulation of sex hormone production in the gonads, adrenals or other tissues (gonadotrophin-independent or peripheral). Delayed puberty is most often constitutional, but hypogonadotrophic (central) and hypergonadotrophic (peripheral) hypogonadism should be considered. In this article, we discuss the clinical and biochemical features of normal and abnormal puberty.